2021
DOI: 10.3390/ijerph18115607
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in Notification and Mortality of Tuberculosis in China, 2004–2019: A Joinpoint and Age–Period–Cohort Analysis

Abstract: Tuberculosis (TB) remains a major public health problem in China and worldwide. In this article, we used a joinpoint regression model to calculate the average annual percent change (AAPC) of TB notification and mortality in China from 2004 to 2019. We also used an age–period–cohort (APC) model based on the intrinsic estimator (IE) method to simultaneously distinguish the age, period and cohort effects on TB notification and mortality in China. A statistically downward trend was observed in TB notification and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 34 publications
(57 reference statements)
7
22
0
1
Order By: Relevance
“…However, after controlling for period and cohort effects, the risk was similar in young and older people. Consistent with Wang’s conclusion [ 16 ], it was even slightly higher in younger adults. It also had come to similar conclusions in Argentina and India [ 13 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, after controlling for period and cohort effects, the risk was similar in young and older people. Consistent with Wang’s conclusion [ 16 ], it was even slightly higher in younger adults. It also had come to similar conclusions in Argentina and India [ 13 ].…”
Section: Discussionsupporting
confidence: 91%
“…Groups born in different generations might have different cohort effects due to the interaction of biological factors, demographic changes, intergenerational effects, and exposure to social events [ 37 ]. The risk was highest in the early cohort in China (especially in eastern), and the later the birth, the lower the risk, consistent with previous studies [ 16 ]. It was mainly due to the early experience of social unrest, frequent wars, economic depression, and other social events.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Age, period, and cohort effects affect the risks of disease incidence and mortality in specific ways, and this analysis can provide information about the underlying causes of cancer incidence and death ( 14 ). There have been several studies using APCM to analyze the incidence or mortality of GBD diseases ( 5 8 , 10 , 14 ). Our study found that the RR remarkably increased with advancing age; specifically, the RR began to increase in the 35–39 age group, continued to rise until age 80–84 in females and 85–89 in males, when it began to decline.…”
Section: Discussionmentioning
confidence: 99%
“…Because the data of EC patients under the age of 20 years old was zero, we excluded this part of the data. The APCM analysis requires five-year intervals for each age group ( 10 ), and we excluded groups 95 years old and older.…”
Section: Methodsmentioning
confidence: 99%